Transient Receptor Potential channels (TRP) in GtoPdb v.2021.3. (2021) - Blair, Nathaniel T.; Carvacho, Ingrid; Chaudhuri, Dipayan; Clapham, David E.; DeCaen, Paul; Delling, Markus; Doerner, Julia F.; Fan, Lu; Ha, Kotdaji; Jordt, Sven E.; Julius, David; Kahle, Kristopher T; et al.
No abstract available